Predictive Value of Neutrophil-to-Limphocyte Ratio for Detecting Nonalcoholic Fatty Liver Disease in Type 2 Diabetes Mellitus Patients - Gede Abhirama Daniswara; Nurhasan Agung Prabowo; Desy Puspa Putri; Laily Shofiyah (Gema Lingkungan Kesehatan, 2026)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic condition characterized by insulin resistance, leading to increased blood glucose levels (hyperglycemia). Insulin resistance is a key factor in the development of nonalcoholic fatty liver disease (NAFLD), a condition defined by excessive hepatic fat accumulation that is not caused by alcohol consumption. NAFLD can progress from simple steatosis to hepatic inflammation and fibrosis. The neutrophil-to-lymphocyte ratio (NLR) is a simple biomarker for systemic inflammation. Elevated NLR values may indicate increased inflammation, such as that observed in NAFLD. This study aimed to determine differences in NLR values in T2DM patients with NAFLD and without NAFLD. This cross-sectional study used secondary data from the medical records of 88 T2DM patients from 2022 to 2024, divided into groups without NAFLD (n=45) and with NAFLD (n=43) based on ultrasonographic liver findings. The Welch t-test was applied to compare NLR values, and receiver operating characteristic (ROC) analysis was used to identify the optimal cut-off value for NLR. The NAFLD group had significantly higher NLR values (mean difference = 3.80; 95% CI: 2.75–5.24; p<0.001), with an AUC of 0.962 (95% CI: 0.915–1.000; p<0.001) and an optimal cut-off value of ≥3.1964 (sensitivity 90.7%; specificity 100%). In conclusion, NLR is significantly elevated in T2DM patients with NAFLD and demonstrates strong discriminatory ability, indicating its potential use as a simple inflammatory biomarker in T2DM managements.